Impact of food processing on the allergenic properties of amylase trypsin inhibitors from wheat - Weegels, Peter L.; America, Antoine H. P. (Frontiers in Allergy, 2023)
Amylase Trypsin Inhibitors (ATIs) play an important role in wheat allergies and potentially in Non Coeliac Wheat Sensitivity. Food processing could be important to mitigate the pathogenic properties of ATIs, e.g. by denaturation, glycation, enzymatic hydrolysis, cross-linking and oxidation and reduction. These modifications also impact the solubility and extractability. The complex solubility behavior of ATI isoforms (water and salt soluble, but also chloroform methanol soluble, solubility depending on the redox state) becomes even more complex upon processing due to denaturation and (bio)chemical modifications. This makes quantitative extraction almost impossible. Also changes in biofunctionality may occur during extraction and the changes in ATI due to food processing will be more difficult to assess. Heat treatment decreases the extractability of ATIs with water, NaCl and other buffer extracts and binding of IgE from wheat allergic persons to ATIs as observed with Western blotting is decreased or absent., IgE binding is reduced whit the total extract in chaotropic and reducing agents but also can increase when the proteins are hydrolyzed by proteases. Fermentation with some species of Fructolactobacilli (FLB) followed by baking decreases the amount of ATIs and IgE binding to ATIs. In yeast fermented bread ATIs decreased similarly in amount, but IgE binding was more prominent, indicating a modification of ATIs affecting epitope recognition. When isolated ATIs are ingested with high ATI degrading FLB the immune response in mice in vivo is less elevated, when compared with ATI without high ATI degrading FLB. Also, when soluble proteins or isolated ATIs are reduced with the thioredoxin/thioredoxin reductase NADPH system, the pathogenic effects on the skin of dogs and one wheat allergic child are decreased. Glycation on the other hand has been shown to potentiate the allergenic properties of ATIs as evidenced by the large increase in IgE binding.The impact of food processing on the pathogenic properties of ATIs is hardly studied in vivo in humans.There seem to be opportunities to mitigate the pathogenic properties in vitro, but potentiation of pathogenic properties is also often observed. This requires a deeper understanding on the impact of food processing on the pathogenicity of ATIs.